Genome-guided purification and characterization of polymyxin A1 from Paenibacillus thiaminolyticus SY20: A rarely explored member of polymyxins - Wu, Ya-ping; Liu, Dong-mei; Liang, Ming-hua; Huang, Yan-yan; Lin, Jin; Xiao, Lan-fang (Frontiers in Microbiology, 2022)
Polymyxin A1 was a rarely investigated member in the polymyxins family produced by Bacillus aerosporus. As a cyclic nonribosomal lipopeptide, it was purified from Paenibacillus thiaminolyticus species for the first time. The producing strain Paenibacillus thiaminolyticus SY20 was separated from Chinese natural fermented bamboo shoots and identified using 16S rRNA sequence homology along with whole genome sequencing. The growth kinetics of antimicrobial agent production was determined and the physicochemical properties of cell-free supernatant (CFS) were evaluated to characterize the properties of antimicrobial agents produced by the strain. Subsequently, the active antimicrobial agent was purified from the supernatant by means of ammonium sulphate graded precipitation, ion-exchange chromatography and C18-H chromatography. The active agent was identified as polymyxin A1 and the structure was elucidated using a combination of liquid chromatography-tandem mass spectrometry (LC-MS/MS), matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS), amino acid analysis and whole genome mining tool. Meanwhile, the biosynthetic gene cluster of polymyxin A1 were also demonstrated in the P. thiaminolyticus SY20 genome. The compound should be further explored for its efficacy and toxicity in vivo to develop its application.